In vitro propagation, shoot regeneration, callus induction, and suspension from lamina explants of Sorbus caloneura - Miaomiao Guo; Qiuying Yu; Daijun Li; Kexin Xu; Zexin Di; Yong Zhang; Yang Yu; Jian Zheng; Yan Zhang (Forestry Research, 2023)
Sorbus caloneura has high ornamental and medicinal value but is endangered, and significant effort is required to preserve this natural resource. In this study, the stem and sterilized leaves of S. caloneura were used to explore the effects of different plant hormones basic medium type, initial callus quality, initial liquid volume, and ratio of old liquid culture medium to new on stem proliferation, regeneration and callus suspension culture. Naphthylacetic acid (NAA) and 6-benzyladenine (6-BA) significantly affected the proliferation of stem tissue. Murashige and Skoog (MS) basal medium supplemented with 1.75 mg/L 6-BA, 0.25 mg/L NAA, and 0.25 mg/L indole butyric acid (IBA) yielded a proliferation rate of 100%, with an average number of adventitious shoots per stem of 4.9. The best callus induction was observed with MS basal medium containing 0.5 mg/L 6-BA, 1 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D), and 0.2 mg/L thidiazuron (TDZ). The adventitious shoots were directly induced by MS basal medium containing 5.0 mg/L 6-BA, 0.5 mg/L NAA, and 1.5 mg/L kinetin (KT) and indirectly induced by medium containing 3.0 mg/L 6-BA, 0.3 mg/L NAA, and 0.1 mg/L TDZ. NAA significantly affected rooting rate, with ideal conditions found to be medium supplemented with 0.2 mg/L NAA and 1.5 mg/L IBA. MS basal medium with 4.5 g of calli and 120 mL of liquid culture medium without retention of the original culture medium yielded the best suspension effect for callus proliferation. Taken together, the results of this study lay a foundation for the breeding, preservation of germplasm resources, and genetic transformation of S. caloneura.